2016
DOI: 10.1080/17512786.2016.1208057
|View full text |Cite
|
Sign up to set email alerts
|

Monologisation as a Quoting Practice

Abstract: This paper explores a particular aspect of journalistic quoting, monologisation. During monologisation, the interactive turn exchange between the journalist and the interviewee is simplified for the article, which is mainly conducted by obscuring the role of the journalist in the original spoken discourse. As a result, the quotations appear to be unprompted, continuous utterances by the interviewee, which in turn has seminal consequences for the interpretation of the quotation. This paper will demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…In other words, transparency has become an increasingly important aspect of journalism that authenticates a claimed professional role, and revealing the real practices might threaten this legitimacy. Among other mechanisms, for example impression management (Goffman, 1959) would discourage journalists from telling their audience that they combined utterances from two or more different places in an interview in order to produce one single quote (Haapanen, 2017a: 23); that they reformulated their interviewees’ unshaped and meandering chit-chat into concise, unambiguous quotes (Haapanen, 2016: Section 4.5); or that on one occasion they had asked an interviewee, ‘Was it a hard situation to accept?’, received the answer ‘Yes’, and then written a direct quote in which the interviewee says, ‘It was hard to accept‘ (Haapanen, 2017b: 9–12).…”
Section: Discussion and Conclusion: Towards Change In The Culture Of ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, transparency has become an increasingly important aspect of journalism that authenticates a claimed professional role, and revealing the real practices might threaten this legitimacy. Among other mechanisms, for example impression management (Goffman, 1959) would discourage journalists from telling their audience that they combined utterances from two or more different places in an interview in order to produce one single quote (Haapanen, 2017a: 23); that they reformulated their interviewees’ unshaped and meandering chit-chat into concise, unambiguous quotes (Haapanen, 2016: Section 4.5); or that on one occasion they had asked an interviewee, ‘Was it a hard situation to accept?’, received the answer ‘Yes’, and then written a direct quote in which the interviewee says, ‘It was hard to accept‘ (Haapanen, 2017b: 9–12).…”
Section: Discussion and Conclusion: Towards Change In The Culture Of ...mentioning
confidence: 99%
“…However, recent production-oriented research on journalistic quoting in a written format (e.g. Havumetsä, 2020; Kuo, 2007; Matsushita, 2016, in press; Nylund, 2006; Satoh, 2001), to which my series of studies (Haapanen, 2011, 2016, 2017a, 2017b, 2017c, 2018, 2020; Haapanen and Perrin, 2019) makes a not inconsiderable contribution, has revealed that the relationship between original interview discourse 2 and the published quoted discourse is by no means so simple and simplistic. To begin with, there is no absolute correspondence between sound waves in the air and graphemes on paper or on screen, and several features of oral communication, such as prosody, do not have any apparent equivalence in writing – if any at all.…”
Section: Quoting: a Seemingly Clear And Simple Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…Its reporting style marks a different approach to the two dailies where journalists’ authorial presence is more clearly visible. The latter approach has been found more commonly in Finnish journalism (Haapanen, 2017; Reunanen and Väliverronen, 2020), and from 2010 to 2015, IL also changes towards it.…”
Section: Story Schemamentioning
confidence: 95%
“…Research in applied sciences is typically triggered by a real-life problem. In my example, which draws on my research project on journalistic quoting (Haapanen 2016a(Haapanen , 2016b(Haapanen , 2016c(Haapanen , 2017a(Haapanen , 2017b(Haapanen , 2018, without explicit cross-references, the trigger was an evident contradiction that appeared between institutional metadiscourse about quoting on the one hand, and actual quoting practices described in existing research on the other. The former, presented in guidebooks, editorial policies and self-regulatory guidelines, presumes that the quoted text is a fairly exact reproduction of what a source used as a text agent has said -if not wordfor-word, then at least in a meaning-for-meaning way.…”
Section: The Study: From a Real-life Problem To Research Questionsmentioning
confidence: 97%